1997
DOI: 10.1128/jvi.71.2.925-933.1997
|View full text |Cite
|
Sign up to set email alerts
|

A novel antibody-dependent cellular cytotoxicity epitope in gp120 is identified by two monoclonal antibodies isolated from a long-term survivor of human immunodeficiency virus type 1 infection

Abstract: Two monoclonal antibodies (MAbs), 42F and 43F, were isolated some 14 months apart from a single long-term survivor of human immunodeficiency virus type 1 (HIV-1) infection. These MAbs were found to be indistinguishable in terms of their isotypes, specificities, affinities, and biological activities. Both 42F and 43F directed substantial antibody-dependent cellular cytotoxicity (ADCC) against cells infected with four divergent lab-adapted strains of HIV-1, but no neutralizing activity against these strains was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Previous studies (1) demonstrated the binding of anti-C5 MAb 43F and anti-CD4 bs MAb IgG1b12 (2) to CD4 Ϫ T cells infected with recombinant vaccinia viruses expressing laboratory-adapted and primary-isolate Envs from clades B and E. Further binding studies of this type were done with additional MAbs of various epitope specificities (data not shown), and the results of these confirmed our earlier impression that, of the three vaccinia virus recombinant primaryisolate Envs tested, the clade E Env of vCB53 was most effi- a All incubations were done under the conditions given in the table using either no Ab or MAb, pooled seropositive sera at 10 Ϫ3 dilution, or 4117C or 41148D at 20 g/ml in a buffer containing 10 mM NaN 3 as described previously (1). An aliquot of washed cells from each of these incubations was then counted for viability, while the remainder were reacted with fluorescein isothiocyanateconjugated goat anti-human IgG at 4°C prior to measurement of fluorescence intensity by flow cytometry as described previously (1). Cell viability after the 4-h incubation at 37°C (final rows of table) was Ն75%, while for all other conditions, it was Ն95%.…”
Section: Binding and Adcc Directed By Mabs Against Targets Chronicallsupporting
confidence: 84%
See 4 more Smart Citations
“…Previous studies (1) demonstrated the binding of anti-C5 MAb 43F and anti-CD4 bs MAb IgG1b12 (2) to CD4 Ϫ T cells infected with recombinant vaccinia viruses expressing laboratory-adapted and primary-isolate Envs from clades B and E. Further binding studies of this type were done with additional MAbs of various epitope specificities (data not shown), and the results of these confirmed our earlier impression that, of the three vaccinia virus recombinant primaryisolate Envs tested, the clade E Env of vCB53 was most effi- a All incubations were done under the conditions given in the table using either no Ab or MAb, pooled seropositive sera at 10 Ϫ3 dilution, or 4117C or 41148D at 20 g/ml in a buffer containing 10 mM NaN 3 as described previously (1). An aliquot of washed cells from each of these incubations was then counted for viability, while the remainder were reacted with fluorescein isothiocyanateconjugated goat anti-human IgG at 4°C prior to measurement of fluorescence intensity by flow cytometry as described previously (1). Cell viability after the 4-h incubation at 37°C (final rows of table) was Ն75%, while for all other conditions, it was Ն95%.…”
Section: Binding and Adcc Directed By Mabs Against Targets Chronicallsupporting
confidence: 84%
“…However, in separate experiments, uncloned MN-infected cells were moderately lysed by 42F (1). Since the apparent affinity of 42F for rgp160 LAI was similar to that of 1125H (1,11), the level of specific lysis directed by 42F was slightly lower than expected against IIIB-infected cells. Nevertheless, the level of specific lysis directed by 42F against SF2and RF-infected cells, especially at lower MAb concentrations, was notably high (Fig.…”
Section: Binding and Adcc Directed By Mabs Against Targets Chronicallmentioning
confidence: 82%
See 3 more Smart Citations